Epidermolytic hyperkeratosis a histological hallmark in the diagnosis of bullous ichthyosiform erythroderma - Mashhood, Asher Ahmed; Iftikhar, Nadia; Sheikh, Zafar Iqbal (Journal of Pakistan Association of Dermatologists, 2016)
Bullous ichthyosiform erythroderma is an uncommon form childhood keratinizing disorder. Early in life it is associated with generalized blistering and erythroderma. Later on it produces rippled type of hyperkeratosis. The diagnosis is confirmed by a very characteristic histopathology. It is described as â€œepidermolytic hyperkeratosisâ€. The purpose of this report is to highlight the features of epidermolytic hyperkeratosis and discuss the differential diagnosis of this histological entity. Â